Knowledge Level And Attitude of Laboratory Staff on Compliance With Personal Protective Equipment (PPE) Use At RSUD Bangil In 2025 - Moh Saheri; Franky Marga Hutama (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Personal Protective Equipment (PPE) is an essential component in preventing exposure to hazardous substances and workplace accidents in laboratories. However, compliance among laboratory personnel in using PPE remains suboptimal. One of the factors influencing compliance is the level of knowledge and individual attitudes toward the importance of PPE use. This study aims to analyse the correlation between knowledge and attitude with PPE compliance among laboratory staff at RSUD Bangil. This research employed a quantitative approach with a cross-sectional design. The sample was determined using a total sampling method, involving 24 laboratory staff members. Knowledge and attitude data were collected using questionnaires, while compliance data were obtained through direct observation. Data were analysed using univariate and bivariate analyses, with the Chi-Square test and Spearman correlation applied. The results showed that most respondents had good knowledge (75%), yet only 50% demonstrated compliance with PPE use. Additionally, the majority of respondents exhibited a negative attitude toward PPE (54.2%). Bivariate analysis revealed a significant correlation between knowledge and compliance (p=0.018) as well as between attitude and compliance (p=0.004). In conclusion, knowledge and attitude significantly influence PPE compliance. Better knowledge and a positive attitude toward PPE use are associated with higher compliance levels. Therefore, strategies to enhance knowledge and foster positive attitudes are essential to improving occupational safety in laboratory settings Keywords : :knowledge, attitude, compliance, personal protective equipment, occupational safety